CASUALISATION OF WORK IN CONSTRUCTION, AND THE PLIGHT OF WORKERS IN BLOEMFONTEIN - Lesiba Mollo; Fidelise EMUZE (Journal of Construction Project Management and Innovation)
Casualisation in the construction industry is influenced by unemployment or lack of decent jobs. Casualisation is defined as the procedure of employing people either on a daily, weekly or monthly basis for an undefined task or specified job without issuing a permanent contract. The study explored the reasons why unemployed people are choosing to become casual workers, and the challenges that they face in the construction industry. A qualitative research approach was used in the study to answer the question “What does it mean to be a casual construction worker in Bloemfontein?” In-depth interviews were used to collect the data. The findings show that unemployed people are choosing to become casual workers because they are failing to get permanent jobs in the private and public sectors due to lack of the requisite education and training. The findings also show that casual workers are victims of exploitation through payment problems. In addition, clients are failing to provide personal protective equipment (PPE) for casual workers. The Department of Labour in South Africa must therefore start to tackle casualisation and compel people who are using casual workers to pay them standard hourly rates (wages) and provide safety protections for them.